Humidity Sensors. Advances in Reliability, Calibration and Application - Cascioli, Vincenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Humidity detection has deep significance for the scientific research surrounding medical care and human performance, and the industrial development of agriculture, geography and automated instruments. This special issue aims to showcase some of the advancements in humidity sensor design and calibration, and its applications. The selected papers cover a variety of humidity sensor-related topics including material science, chemistry and industrial engineering. Through dedicated contributions from peer reviewers and the editorial team, this book aims to offers reader some insight into the field of humidity sensor development and use.